РОЗВ'ЯЗАННЯ ДВОЇСТОЇ ЗАДАЧІ ОПТИМАЛЬНОГО КЕРУВАННЯ НОРМАЛЬНИМИ РЕЖИМАМИ EEC З ЗАСТОСУВАННЯМ НЕЙРО-НЕЧІТКОГО МОДЕЛЮВАННЯ - Петрушенко, О.Ю.; Петрушенко, Ю.В.; Рубаненко, О.О. (Інститут електродинаміки НАН України, Київ, 2012)
Analyzed the possibility of dvoistoy problem solving of the optimal control  normal regimes of EPS with using neurofuzzy modeling. Proposed algorithm of dvoistoy problem  solving  of the optimal control normal regimes of EPS. This algorithm based on presentation of basis similarity criterion with use function membership in the target function (planned power loss) of propering sets.  References 3.